2019
DOI: 10.14735/amko2019124
|View full text |Cite
|
Sign up to set email alerts
|

Gorlin-Goltz syndrome

Abstract: Východiská: Gorlinov-Goltzov syndróm je autozómovo dominantne dedičné ochorenie charakteristické predispozíciou k rôznym typom nádorov. Klinicko-patologické nálezy syndrómu sú veľmi pestré, pričom mnohé symptómy sa začínajú prejavovať až v určitom období života. Prípad: Autori opisujú prípad muža, ktorý sa vo veku 34 rokov dostavil na dermatologické vyšetrenie s mnohopočetnými tumoróznymi léziami kože. Ich vývoj začal pozorovať približne od 30. roku života a odvtedy sa ich počet zvyšoval. Histologicky išlo o b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 7 publications
0
8
0
1
Order By: Relevance
“…From a prognostic standpoint, early diagnosis and appropriate treatment are critical. If diagnosed, lifelong care with interdisciplinary medical collaboration is necessary [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…From a prognostic standpoint, early diagnosis and appropriate treatment are critical. If diagnosed, lifelong care with interdisciplinary medical collaboration is necessary [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac fibromas comprise less than 5% of primary tumors of the heart [ 2 ] and represent the second most common tumor of the heart in children after rhabdomyoma [ 8 , 9 ]. They are exceptionally rare in adults [ 6 ] and may be associated with Gorlin-Goltz syndrome (multiple nevoid basal cell carcinomas, mandibular cysts, fused ribs, calcification of the falx cerebri, odontogenic keratocysts) [ 10 , 11 ]. Fibromas can be asymptomatic or present with significant arrhythmias, ventricular tachycardia being the most common type [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, BCCs were presented in only 38.4% of American people with dark skin and 37.8% of the Japanese people. The authors concluded that the phenotypic diversity presented can be explained by mutations of the PTCH gene and impact of the environment of each ethnic group [15]. 1 1.8×1.6 cm in dimension, with a flat grayish lesion on its surface, 1.5 cm in largest diameter 2 1×0.8 cm in dimension.…”
Section: Discussionmentioning
confidence: 99%